2002
DOI: 10.3177/jnsv.48.371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Habitual Chitosan Intake on Bone Mass, Bone-Related Metabolic Markers and Duodenum CaBP D9K mRNA in Ovariectomized SHRSP Rats.

Abstract: SummaryWe have demonstrated that the habitual intake of chitosan can decrease bone mass in ovariectomized (OVX) SHRSP rats fed a low-Ca diet (0.1%). In the present study, we examined both the etiology of bone loss induced by dietary chitosan and the preventive ef fect of vitamin C supplementation. Rats were OVX and maintained on one of the following diets for 6 wk: 10% cellulose (CE), 10% chitosan (CH) or 10% chitosan with sodium ascor bate (CHVC). CH caused a significant reduction in bone mineral density (BMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…In addition to the increased 1,25 (OH)2 vitamin D levels, significant decreases in serum phosphorus were also seen in male and female rats. Although intestinal absorption of phosphorus was not measured in this study, chitosan has been observed by others to cause a significant reduction in intestinal phosphorus absorption 64 . Low phosphorus concentrations stimulate 1,25 (OH)2 vitamin D production by the kidney, therefore the increased levels of 1,25 (OH)2 vitamin D observed in this study may be the result of the low phosphorus levels.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition to the increased 1,25 (OH)2 vitamin D levels, significant decreases in serum phosphorus were also seen in male and female rats. Although intestinal absorption of phosphorus was not measured in this study, chitosan has been observed by others to cause a significant reduction in intestinal phosphorus absorption 64 . Low phosphorus concentrations stimulate 1,25 (OH)2 vitamin D production by the kidney, therefore the increased levels of 1,25 (OH)2 vitamin D observed in this study may be the result of the low phosphorus levels.…”
Section: Discussionmentioning
confidence: 66%
“…Also, standard osteoporosis studies using rat models commonly utilize ovariectomized animals, which mimics the conditions of menopause and generally increases rates of bone remodeling and bone loss. Ovariectomized SHRSP rats fed 10% chitosan alongside a low calcium diet exhibited decreased bone mineral density and increased femur stiffness 64 . Following ovariectomy, bone loss in the femurs, specifically the femoral neck, is still not observed until a minimum of 30 days postprocedure 75 .…”
Section: Discussionmentioning
confidence: 93%
“…When tested at chitosan to fat 1:40, the ratio often used as a dietary supplement, higher tap density chitosan showed an improved fat-binding capacity at around a two-fold increase. Interestingly, 2100 kDa high density (HD1P) could maintain the highest oil entrapment, ranging between 0.77 and 27.50 g oil/g chitosan depending on the interaction ratios [100].…”
Section: Pro-health Properties (Antihyperlipidemic Mineral Absorption Bodyweight Reduction)mentioning
confidence: 99%
“…On the other hand, dietary fiber may influence the availability of minerals, such as calcium, magnesium [154] and iron [155]. Animal studies have found that dietary chitosan possibly arrests the absorption of calcium [156,157].…”
Section: Digestive Chemical Model and Glucose Calcium And Iron Retenmentioning
confidence: 99%